The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s0036-46652015000600006
|View full text |Cite
|
Sign up to set email alerts
|

Virological and Serological Diagnosis of Rabies in Bats From an Urban Area in the Brazilian Amazon

Abstract: The outbreaks of rabies in humans transmitted by Desmodus rotundus in 2004 and 2005, in the northeast of the Brazilian State of Para, eastern Amazon basin, made this a priority area for studies on this zoonosis. Given this, the present study provides data on this phenomenon in an urban context, in order to assess the possible circulation of the classic rabies virus (RABV) among bat species in Capanema, a town in the Amazon basin. Bats were collected, in 2011, with mist nets during the wet and dry seasons. Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…This species was collected in culverts, abandoned buildings, and nets while flying at night. A high percentage of seropositive bats was observed in this species (31.9%), which is in concordance with Oliveira et al 13 .…”
Section: /6supporting
confidence: 92%
See 2 more Smart Citations
“…This species was collected in culverts, abandoned buildings, and nets while flying at night. A high percentage of seropositive bats was observed in this species (31.9%), which is in concordance with Oliveira et al 13 .…”
Section: /6supporting
confidence: 92%
“…No significant differences were recorded between sex and age of bats in accordance with Thoisy et al 9 , Almeida et al 11 , and Costa et al 12 . However, Oliveira et al 13 found significantly higher proportions of males and adults that were seropositive for rabies.…”
Section: /6mentioning
confidence: 96%
See 1 more Smart Citation
“…Even so, the ample geographic distribution of D . rotundus and the free circulation of the virus among bats are two of the factors that contribute most to the persistence of the disease in the Brazilian Amazon region [ 51 , 52 ]. The persistence of outbreaks in certain areas is also related directly to the performance of the local public health authorities responsible for the control of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent decline may reflect lower levels of viral circulation in the bat population and may be responsible for the lower seroprevalence proportion demonstrated in this contemporary study (8.6%), as compared the previous study conducted in the 1970s (12.8%) [29]. Conversely, studies conducted in South America demonstrate an inverse relationship between RABV prevalence and RVNA seroprevalence [43,44,75]. This may be attributed to the protective effect of herd immunity and death of virus-infected individuals, with the virus less able to establish infection and sustain bat to bat transmission due to increasing numbers of immune individuals.…”
Section: Rabv Prevalence Ratesmentioning
confidence: 54%